The prevalence and prescribing patterns of benzodiazepines and Z-drugs in older nursing home residents in different European countries and Israel: retrospective results from the EU SHELTER study - Lukačišinová, Anna; Fialová, Daniela; Peel, Nancye May; Hubbard, Ruth Eleanor; Brkic, Jovana; Onder, Graziano; Topinková, Eva; Gindin, Jacob; Shochat, Tamar; Gray, Leonard; Bernabei, Roberto (BMC geriatrics, 2021)
BACKGROUND: Benzodiazepines (BZDs) and Z-drugs have high potential for developing frequent adverse drug events in older adults (e.g., psychomotor sedation, drug-related dementia, deliria, drug dependence, etc.). Knowledge of the prevalence and patterns of the use of BZDs/Z-drugs in vulnerable older patients is important in order to prevent and reduce the burden caused by their drug-related complications. Our study focused on international comparisons of the prevalence, country-specific prescribing patterns and risk factors of regular BZD/Z-drug use in nursing home (NH) residents. METHODS: This cross-sectional study retrospectively analysed data of 4156 NH residents, prospectively assessed in the Services and Health in the Elderly in Long TERm care (SHELTER) project conducted from 2009 to 2014. Residents aged 65+ in 57 NHs in 7 European countries and Israel were assessed by the InterRAI Long-Term Care Facilities instrument. Descriptive statistics and multiple logistic regression models were used to describe the country-specific prevalence, patterns and risk factors of BZD/Z-drug use. RESULTS: The mean age of the participants was 83.4 ± 9.4 years, 73% were female and 27.7% used BZDs/Z-drugs. The prevalence of BZD/Z-drug use differed significantly across countries, ranging from 44.1% in Israel to 14.5% in Germany. The most frequently prescribed were zopiclone (17.8%), lorazepam (17.1%) and oxazepam (16.3%). Lorazepam, oxazepam and diazepam were used in most of the countries. Brotizolam, temazepam and zolpidem showed highest prevalence in Israel (99.4% of all regular users of this medication in the sample), the Netherlands (72.6%) and France (50.0%), respectively. Residing in Israel was the most significant factor associated with the use of BZDs/Z-drugs or BZDs only (odds ratio [OR] 6.7; 95% confidence interval [CI] 4.8-9.2 and OR 9.7, 95%CI 6.5-14.5, respectively). The use of Z-drugs only was most significantly associated with residing in France (OR 21.0, 95%CI 9.0-48.9). CONCLUSIONS: Despite global recommendations and warnings, the preference for and extent of use of individual BZDs and Z-drugs in vulnerable NH residents differ significantly across countries. The strong association with country of residence compared to clinical and functional factors denotes that prescribing habits, social, cultural, behavioural, and regulatory factors still play an important role in the current diverse use of these medications.
Keywords: Nursing homes; léčivé přípravky; Nursing Homes; Humans; Netherlands; Pharmaceutical Preparations; prevalence; Nizozemsko; Female; Aged; senioři; lidé; Europe; Germany; Německo; Francie; Izrael; France; benzodiazepiny; ženské pohlaví; Male; Retrospective Studies; Benzodiazepines; Aged, 80 and over; Cross-Sectional Studies; Z-drugs; Prevalence; senioři nad 80 let; retrospektivní studie; mužské pohlaví; Israel; průřezové studie; pečovatelské domovy; Evropa